Group norms and the Brac village organization—enhancing social capital baseline - Qayum, Nayma; Samadder, Mrinmoy; Rahman, Rehnuma (BRAC Research and Evaluation Division, 2022)
As an NGO, BRAC adopts a holistic development approach centred on the Village Organization (VO), a group of female microfinance clients. In order to upgrade the VO integrity and norms, BRAC’s Social Development (SD) Program (currently renewed as Community Empowerment Program or CEP) introduced the Enhancing Social Capital (ESC) project in 2010. This study used social capital as an organizing framework to capture VO members’ group behaviour, and their current status along with program activities. The study compared the status of intervention VOs with comparison VOs. Data were derived from 728 VO meeting observations and 2445 semi-structured interviews of VO members. It found that geographical and infrastructural factors explained some differences between intervention and control groups. VO presidents performed better than the general VO members (GM). VO group solidarity, individual trust, the VO’s client-friendliness, and years of education influenced the extent to which VO members adhered to good VO group norms.